INCREASING ECONOMIC EFFICIENCY BASED ON THE USE OF DIGITAL TECHNOLOGIES IN INDUSTRIAL ENTERPRISES (Marketing Journal, 2025)
This article examines the issues of improving the economic efficiency of industrial enterprises through the use of digital technologies. It provides a detailed analysis of digital transformation processes, strategies for enhancing production efficiency, st ages of implementing smart technologies, and their impact on production activities. Additionally, it highlights the opportunities to increase productivity and efficiency in agriculture through the adoption of innovative technologies. The research findings indicate that digital transformation has a positive effect on the competitiveness and economic stability of enterprises. 294
Keywords: digitalization; digital enterprise; digital transformation; cloud technology; big data; digital transformation models; process model; network model; technology model; matrix model